Perpetrator Abuse Narcotics Ongan Goal 1 Based on Perspective Sociology Law - Ferliana Syahputro Wibiyanto; Albertus Sentot Sudarwanto (MultiTech Publisher, 2024)
Narcotics is drug or material Which beneficial in field treatment, health services and scientific development, but on the other hand it can give rise to dependence Which very harm if used without there is control, strict and thorough supervision... As in the previous case researchers found in South Labuhabatu district, North Sumatra province, namely decision number: 792 K/PID.SUS/2017. In this case a defendant who named Misniar Wati Harahap alias Wati is a narcotics criminalWhere should judge consider verdict Which given to defendant.And should judge aggravate punishment Which given to convict. Type study in This legal research is normative or doctrinal legal research. In Judgment Number 792 K/PID.SUS/2017, the author agrees with the Decision of the Panel of Judges which judge that defendant violate Chapter 111 paragraph (1), 114 paragraph (1), 127 Paragraph (1) letter a Law. R.I. No. 35 of 2009 concerning Narcotics, because the elements of This article was proven as a fact before the Court, so It is correct that the Amar/Contents of the Judges' Decision stated that MISNIAR WATI HARAHAP alias WATI has been legally and convincingly proven guilty of committing criminal offense